Effects of a Dalcroze-based Music Intervention on the Mood of Older Adults - Olejar, Aleksandra (Université d'Ottawa | University of Ottawa, 2026)
Older adults may experience physical, cognitive, social, and mental health challenges associated with aging, which can affect their daily functioning and overall quality of life. These factors have contributed to increased interest in supportive, non-pharmaceutical interventions that may help address these challenges. The present study used a Dalcroze Eurhythmics program as the non-pharmaceutical intervention. As part of a large international multi-site project, the study conducted for this thesis builds upon the positive outcomes observed during the feasibility study on Dalcroze Eurhythmics programs for older adults. The feasibility study, which I conducted from May to August 2023 at The Royal Ottawa Mental Health Centre, Geriatrics Outpatient Unit, served as the quality improvement phase of the larger project. Therefore, focusing on the music program’s immediate effects on mood represents an appropriate step in advancing understanding of its effects. The purpose of the present study was to examine the immediate effects of each lesson on participants’ mood, measured through pre- and post-lesson scores on the Positive and Negative Affect Schedule (PANAS). Additional measures, including the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS), the Standardized Mini-Mental State Examination (SMMSE), and the Centre of Excellence Self-Administered Questionnaire (CESAM), provided contextual information for interpreting the findings. Semi-structured interviews were conducted to explore participants’ experiences with the music program in more depth and how their perceived effects of the program on mood aligned with questionnaire results. The study also aimed to contribute to the growing body of knowledge regarding effective non-pharmaceutical interventions for older adults by incorporating evidence-based results. Using a Single-Case Experimental Design (SCED), the present study examined two participants (ages 85 and 84) who took part in an 18-week study that included a Dalcroze Eurhythmics program. The results showed consistent immediate increases in positive affect after each lesson, alongside smaller but noticeable reductions in negative affect. Participants’ interview responses aligned with these findings and offered additional insight into their experiences with the music program and its effects on mood.
Keywords: Dalcroze Eurhythmics; music intervention; older adults; mood; single-case experimental design; mixed-methods; music and movement